ETHERNES: A new design of radionuclide source-based thermal neutron facility with large homogeneity area. (January 2016) - Bedogni, R.; Sacco, D.; Gómez-Ros, J.M.; Lorenzoli, M.; Gentile, A.; Buonomo, B.; Pola, A.; Introini, M.V.; Bortot, D.; Domingo, C.
Abstract: A new thermal neutron irradiation facility based on an 241 Am–Be source embedded in a polyethylene moderator has been designed, and is called ETHERNES (Extended THERmal NEutron Source). The facility shows a large irradiation cavity (45 cm×45 cm square section, 63 cm in height), which is separated from the source by means of a polyethylene sphere acting as shadowing object. Taking advantage of multiple scattering of neutrons with the walls of this cavity, the moderation process is especially effective and allows obtaining useful thermal fluence rates from 550 to 800 cm −2  s −1 with a source having nominal emission rate 5.7×10 6  s −1 . Irradiation planes parallel to the cavity bottom have been identified. The fluence rate across a given plane is as uniform as 3% (or better) in a disk with 30 cm (or higher) diameter. In practice, the value of thermal fluence rate simply depends on the height from the cavity bottom. The thermal neutron spectral fraction ranges from 77% up to 89%, depending on the irradiation plane. The angular distribution of thermal neutrons is roughly isotropic, with a slight prevalence of directions from bottom to top of the cavity. The mentioned characteristics are expected to be attractive for the scientific community involved in neutron metrology, neutron dosimetry and neutron detector testing.